Effects of solar ultraviolet radiation on terrestrial ecosystems. Patterns, mechanisms, and interactions with climate change - Ballare, Carlos Luis (2011)
Ultraviolet radiation (UV) is a minor fraction of the solar spectrum reaching the ground surface. In this assessment we summarize the results of previous work on the effects of the UV-B component (280-315 nm) on terrestrial ecosystems, and draw attention to important knowledge gaps in our understanding of the interactive effects of UV radiation and climate change. We highlight the following points: (i) The effects of UV-B on the growth of terrestrial plants are relatively small and, because the Montreal Protocol has been successful in limiting ozone depletion, the reduction in plant growth caused by increased UV-B radiation in areas affected by ozone decline since 1980 is unlikely to have exceeded 6%. (ii) Solar UV-B radiation has large direct and indirect (plant-mediated) effects on canopy arthropods and microorganisms. Therefore, trophic interactions (herbivory, decomposition) in terrestrial ecosystems appear to be sensitive to variations in UV-B irradiance. (iii) Future variations in UV radiation resulting from changes in climate and land-use may have more important consequences on terrestrial ecosystems than the changes in UV caused by ozone depletion. This is because the resulting changes in UV radiation may affect a greater range of ecosystems, and will not be restricted solely to the UV-B component. (iv) Several ecosystem processes that are not particularly sensitive to UV-B radiation can be strongly affected by UV-A (315-400 nm) radiation. One example is the physical degradation of plant litter. Increased photodegradation (in response to reduced cloudiness or canopy cover) will lead to increased carbon release to the atmosphere via direct and indirect mechanisms.